2006
DOI: 10.1079/bjn20051668
|View full text |Cite
|
Sign up to set email alerts
|

Intake of high levels of vitamin A and polyunsaturated fatty acids during different developmental periods modifies the expression of morphogenesis genes in European sea bass (Dicentrarchus labrax)

Abstract: The effect of the feeding period on larval development was investigated in European sea bass larvae by considering the expression level of some genes involved in morphogenesis. Larvae were fed a control diet except during three different periods (period A: from 8 to 13 d post-hatching (dph); period B: from 13 to 18 dph; period C: from 18 to 23 dph) with two compound diets containing high levels of vitamin A or PUFA. European sea bass morphogenesis was affected by these two dietary nutrients during the early st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 39 publications
9
81
2
1
Order By: Relevance
“…Amplifications were performed from RNA samples used for microarray analysis. Reverse transcription and real time PCR were monitored as previously described (Villeneuve et al, 2006) using the MyIQ single color real time PCR detection system (Biorad). Reverse transcription products were diluted to 1/300, and 5 μl were used for each real-time PCR reaction.…”
Section: Real Time Pcr Analysismentioning
confidence: 99%
“…Amplifications were performed from RNA samples used for microarray analysis. Reverse transcription and real time PCR were monitored as previously described (Villeneuve et al, 2006) using the MyIQ single color real time PCR detection system (Biorad). Reverse transcription products were diluted to 1/300, and 5 μl were used for each real-time PCR reaction.…”
Section: Real Time Pcr Analysismentioning
confidence: 99%
“…HERNÁNDEZ et al (2013) reported variations in the number of vertebrae in Rhamdia quelen larvae from different biotypes reared under laboratory conditions. Also, VILLENUEVE et al (2006) observed a high incidence of supernumerary vertebrae in D. labrax larvae fed with excess of fatty acids in the diet. The high variability in meristic features found in farmed fish can be attributed to the interaction between genetic and environmental factors (BOGLIONE et al, 2001;KOUMOUNDOUROS et al, 2001, HERNÁNDEZ et al, 2013.…”
Section: Discussionmentioning
confidence: 93%
“…Trabajos previos demostraron que diferentes componentes alimenticios pueden desencadenar trastornos en los procesos de desarrollo y diferenciación celular (Cahu et al, 2003;Lall & Lewis-McCrea, 2007). La utilización de vitamina A (Villeneuve et al, 2006;Fernández et al, 2008;Mazurais et al, 2009), vitamina C (Merchie et al, 1997;Wang et al, 2002;Darias et al, 2011) y vitamina D (Darias et al, 2010), entre otras, tienen una marcada relación con los niveles dietarios y la incidencia de malformaciones en las larvas. Sin embargo, estas sustancias se suministran a niveles superiores a los requeridos por las larvas (NRC, 1993), con la finalidad de compensar la pérdida de estos compuestos durante la fabricación de los alimentos o por la rápida lixiviación (principalmente en vitaminas hidrosolubles) (Lazo, 2000;Guillaume et al, 2004).…”
Section: Discussionunclassified